Analysis of Selected Parameters of Bottled Water in Poland - Lada, Agata; Paulina, Bożek ("Intercultural Dialogues" Transactions, 2025)
Water is essential for life. People use it in almost every aspect of their lives. Bottled water available on the market for consumption should be free from dangerous microorganisms and have a stable chemical composition. The presented study aimed to observe changes in selected water quality parameters in various conditions after opening a bottle of water. Four types of bottled water with different degrees of mineralization and carbon dioxide saturation were analyzed. The studies were performed according to the standards and procedures: PN-ISO 6059: 1999, PN-ISO 6332: 2001, PN-ISO 7150-1: 2002, PN-EN ISO 10523: 2012, PN-EN ISO 6222: 2004, Method 8149 – 1-(2-Pyridylazo)-2-Naphthol PAN Method. A microbiological analysis was carried out in terms of the total number of microorganisms at a temperature of 22˚C at different time intervals after opening the bottle. The analysis of statistical tests allowed for a comparison of different types of water in terms of its resistance to secondary microbiological contamination after opening the bottle, as well as for the formulation of conclusions regarding the time of storage of water in an open bottle, after which the water does not meet the quality requirements in the analyzed range. The tested waters were also subjected to physicochemical analysis. The total content of calcium and magnesium was determined using the titration method with EDTA, ammonium nitrogen, manganese and iron using the spectrometric method, pH was measured to check the water quality and whether the tested water meets the requirements contained in the Regulation of the Minister of Health of 31 March 2011 on natural, spring waters and table waters (Journal of Laws 01.85.466). The determined physicochemical parameters of selected bottled waters were intended to characterize and determine differences in the chemical composition of these waters and to demonstrate. The obtained test results were subjected to statistical analysis, calculating the arithmetic mean, median, dispersion, standard deviation and relative standard deviation. The conducted water analysis was compared with the results obtained for tap water in Tarnow, which were made available by Tarnowskie Wodociągi Spółka z o.o.